Rescaled-expansive flows: unstable sets and topological entropy - Arbieto, Alexander; Artigue, Alfonso; Rego, Elias (Topological Methods in Nonlinear Analysis, 2025)
In this work, we introduce and explore a rescaled theory of local stable and unstable sets for rescaled-expansive flows and its applications to topological entropy. We introduce a rescaled version of the local unstable sets and the unstable points. We find conditions for points of the phase space to exhibit non-trivial connected pieces of such unstable sets. We apply these results to the problem of proving positive topological entropy for rescaled-expansive flows with non-singular Lyapunov stable sets.